Spectral-luminescent properties of bromcresol purple - Bezlepkina, N. P. (Russian physics journal)
The influence of the solvent on the spectral-luminescent properties of bromcresol purple (BCP) has been studied. The spectral characteristics of BCP: half-width, Stokes shift, molar absorption coefficient, intrinsic excited state lifetime, and oscillator strength are determined. Using the Lippert equation, the dependence of the Stokes shift of BCP on the orientational polarizability of the solvent has been constructed. An analysis of the experimental data showed that the position of the maximum of the BCP absorption band in the region of 350–480 nm correlates with the acceptor number of the solvent: with a decrease in the acceptor number, the band maximum shifts toward shorter wavelengths (water ethanol toluene acetone). The lowest absorption capacity of BCP was registered in toluene. Using the Lippert–Mataga equation, the change in the dipole moment in polar protic solvents (16.2 D) upon excitation was determined, which is higher than in aprotic solvents (10.4 D) due to the formation of H-bonds.